Relationship between type of work and metabolic syndrome among the National Electoral Board’s employees. Lima, 2013 - González-Vereau, Alicia (2017)
Objective: To determine the relationship between public employees’ type of work and the development of metabolic syndrome. Materials and methods: Descriptive cross-sectional observational study. The sample consisted of employees of the National Electoral Board (JNE), Lima office, who underwent their 2013 occupational medical evaluation and were assessed according to the Adult Treatment Panel III (ATP - III) criteria, as amended in 2005. Data collection was obtained from the employees’ occupational medical records. Results: Three hundred twenty-two (322) employees were evaluated. The metabolic syndrome prevalence was 2.17%. The administrative sector was affected in 2.28% (p = 1.0) compared to the non-administrative sector which showed no cases. The highest prevalence of metabolic syndrome was found in 30 - 39 years old employees (3.7%) (p=0.495). The study showed statistical significance in relation to male gender (p= 0.019). Conclusions: In administrative employees of the JNE, there was no relationship between the type of work and the development of metabolic syndrome. Male gender was associated with metabolic syndrome.